Dynamic Trends in Aquatic Product Supply and Consumption in China: Implications for Sustainable Diets and Environmental Impact Reduction - Wanni Yang (Foods)
Aquatic foods play a pivotal role in transforming food systems. As the world’s leading producer, consumer, and trader of aquatic products, China’s potential for sustainable supply and consumption is critical to understand. The aim of this study was to depict the dynamic trends of aquatic products and the consequences of sustainable diets and environmental impacts. A panel dataset about Chinese aquatic products covering the period from 1952 to 2023 was drawn for analysis. Diet sustainability was assessed with the deviation from the Dietary Guidelines for Chinese Residents (2022) and EAT-Lancet recommendations. The environmental impacts of aquatic products’ supply and consumption were assessed using carbon footprints and water footprints. The findings reveal that aquatic products’ supply increased from 4.65 million tons to 71.16 million tons from 1978 to 2023, and annual aquatic food consumption per capita increased from 3.50 kg in 1978 to 15.20 kg. While overall supply meets consumption needs, structural imbalances persist at the provincial level. Over time, the influence of marine fishery products has declined from 1.06 million tons (63.63%) in 1952 to 35.85 million tons (50.38%) in 2023, whereas offshore aquaculture shows promising potential for meeting future supply demands (23.96 million tons in 2023, accounting for 66.82% of marine fishery production). To align with healthy dietary goals and environmentally sustainable food systems, provincial aquatic food demand across China was adjusted. The carbon footprints and water footprints of both current and adjusted consumption patterns were also assessed. The results indicate that adjusting consumption based on the Dietary Guidelines for Chinese Residents (2022) and EAT-Lancet recommendations could reduce environmental impacts to different degrees. The findings could offer valuable references and insights into developing sustainable strategies in aquatic product management and advancing food system transformation.